The Social Responsibility of Women During the New Order: Between Family and Community - Amini, Mutiah (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Andalas, 2024)
This paper discusses the lives of Indonesian women within the confines of family and community amidst the strengthening of programs pertaining to women’s empowerment that were launched by the New Order administration from 1966 to 1998. The significant questions this research addresses are: 1) How was the empowerment programs conducted? and 2) How did the programs affect the lives of women within their families and communities. The results of this study showed that during the New Order administration, it became apparent that women lost their autonomy as burdens were stacked on them within their families and communities. Through empowerment programs, women were expected to be robust and independent; however, because the New Order programs were structurally designed to be heavily centralized, they instead reinforced the existing traditional social construction. As the women subsequently bore heavy burdens to thrive accomplishment in both familial and communal spheres, the introduced programs worked instead to repressively narrow women’s chances for autonomy. This historical research study utilized a variety of data in the forms of documents, both archival or memoir types.